Correlation of serum ferritin level in transfusion-dependant thalassemia major patients: a study at a medical college affiliated hospital in Gujarat region - Bhalodiya, Vijay R.; Valiya, Lalji G.; Mehta, Niyati A.; Padhariya, Bhavin B. (International Journal of Contemporary Pediatrics, 2023)
Background: Beta thalassemia is one of the most common causes of inherited disorder in the world. In India, around 65000-70000 cases of thalassemia are present currently and every years around 9000-10000 new cases are added. Measurement of serum ferritin level gives an idea about when to start iron chelation therapy, which will reduce the concentration of iron in the serum and thereby prevents the multiple organ damages. Methods: A prospective hospital based study was conducted on 100 children having beta thalassemia major. These children were regularly transfused at our hospital and their serum ferritin level were measured by ELISA based assay. Detailed transfusion history and demographic profile were recorded and compared with serum ferritin level. Results were analyzed with SPSS software and Microsoft Excels. Results: In present study, mean serum ferritin level in 0-5 year age group was1262 µg/l, in 6-10 years age group was 1963.44µg/l and in 11-18 years age group was 2387.43µg/l. On applying ANOVA test, it was evident that there was a statistically significant correlation between increased serum ferritin level with increasing age of the patient as well as with increasing number of a total blood transfusion. Conclusions: High serum ferritin level in beta thalassemia is associated with increasing age of children as well as with increasing transfusion dependency. Serum ferritin measurement at regular interval helps in determining the ideal timing to start iron chelation therapy in transfusion dependant thalassemic patients.